Economic and cultural correlates of cannabis use among mid-adolescents in 31 countries. - Bogt, T ter; Schmid, H; Nic Gabhainn, Saoirse; Fotiou, A; Vollebergh, W (Addiction, 2006)
The aim of this study was to examine cannabis use among mid-adolescents in 31 countries and associations with per-capita personal consumer expenditure (PCE), unemployment, peer factors and national rates of cannabis use in 1999. The authors used results from the Health Behaviour in School-aged Children (HBSC) study, a collaborative cross-national research study supported by WHO/Europe. The sample was nationally representative and consisted of a self-report survey with 22,223 male and 24,900 female 15-year-olds. Country characteristics were derived from publicly available economic databases and previously conducted cross-national surveys on substance use. Anglo-American countries (Canada, United Kingdom, United States) and Switzerland and Greenland have relatively high prevalences of life-time cannabis use, whereas most countries from eastern and northern Europe, except Czech Republic, Hungary, Slovenia and Ukraine, have a low prevalence. Mediterranean countries, except Spain and to a lesser extent Italy and Portugal (Malta, Israel, Greece and Macedonia) also tend to have relatively low prevalence estimates. Most western European countries rank in between (Belgium, Denmark, France, Germany, Ireland, the Netherlands). On the whole, boys have higher prevalence rates than girls, gender differences generally being greatest in the countries from eastern and southern Europe. Overall, life-time prevalence and frequent use are associated with PCE, perceived availability of cannabis (peer culture) and the presence of communities of older cannabis users (drug climate). The authors conclude that As PCE increases, cannabis use may be expected to increase and gender differences decease. Cross-national comparable policy measures should be developed and evaluated to examine which harm reduction strategies are most effective.